Reich on Tape: The Performance of Violin Phase. Issue 1 (February 2017) - AUNER, JOSEPH
ABSTRACT: The score of Steve Reich's Violin Phase specifies that the performer is to recapitulate aspects of the composer's creative process in the studio. Working with a four-channel tape recorder, the violinist and a sound engineer are given detailed directions for creating the basic tape loop that generates the performance tape used in live performance. And yet – no doubt due to the scarcity of appropriate tape recorders – most present-day performers of Violin Phase use looping hardware or software that make it possible to dispense with many of the instructions in the score, including the necessity of having the engineer on stage. That this significant change in performance practice seemingly passes for the most part without notice demonstrates how the decades-long ubiquity of tape has been replaced by a kind of invisibility, through which the particularities of the medium have been subsumed into more generalized notions of fixed media. I argue that the specific materialities of tape and tape machines are not incidental to Violin Phase, but are central to its composition, performance, and reception. A focus on the role of tape, and indeed on the roll of tape itself, can illuminate this and other pieces as well as Reich's deep involvement with music technologies throughout his career.